PENGETAHUAN PEREMPUAN PENANGKAP GURITA DI DESA LANOSANGIA KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Firawati Firawati; Ashmarita Ashmarita (KABANTI : Jurnal Kerabat Antropologi, 2023)
This research aims to find out how the knowledge of women octopus catchers. This research technique is direct research, involved observation methods and in-depth interviews. The results showed that knowledge about octopus obtained from their parents and from their experience in catching octopus. classify knowledge about octopus into several, namely knowledge about the types of octopus, namely kuita type octopus (white octopus) which is further divided into two, namely kuita tama (male octopus) and kuita cina (female octopus), suda type octopus (red octopus), imbu (blue ring octopus). Knowledge about octopus habitat is divided into two, namely nests with octopus and nests without octopus. Knowledge about the octopus season, namely that octopus will be abundant during the wula bara (Western season) and when the mo'oci (low tide) is large. Knowledge about how to catch octopus, which consists of two: how to catch octopus with mekanciu (using hooks and awls) and how to catch octopus with mepoco-poco (using pocong-pocong).